Effect of recovery interventions on cycling performance and pacing strategy in the heat - de Pauw, K.; Roelands, B.; Vanparijs, J.; Meeusen, R. (International Journal of Sports Physiology and Performance, 2014)
Purpose: To determine the effect of active recovery (AR), passive rest (PR), and cold-water immersion (CWI) after 90 min of intensive cycling on a subsequent 12-min time trial (TT2) and the applied pacing strategy in TT2. Methods: After a maximal test and familiarization trial, 9 trained male subjects (age 22 ± 3 y, VO2max 62.1 ± 5.3 mL/min·kg) performed 3 experimental trials in the heat (30°C). Each trial consisted of 2 exercise tasks separated by 1 h. The first was a 60-min constant-load trial at 55% of the maximal power output followed by a 30-min time trial (TT1). The second comprised a 12-min simulated time trial (TT2). After TT1, AR, PR, or CWI was applied for 15 min. Results: No significant TT2 performance differences were observed, but a 1-sample t test (within each condition) revealed different pacing strategies during TT2. CWI resulted in an even pacing strategy, while AR and PR resulted in a gradual decline of power output after the onset of TT2 (P = .046). During recovery, AR and CWI showed a trend toward faster blood lactate ([BLa]) removal, but during TT2 significantly higher [BLa] was only observed after CWI compared with PR (P = .011). Conclusion: The pacing strategy during subsequent cycling performance in the heat is influenced by the application of different postexercise recovery interventions. Although power was not significantly altered between groups, CWI enabled a differently shaped power profile, likely due to decreased thermal strain.